Regional economic analysis for practitioners - Bendavid-Val, Avrom (New York : Praeger, 1972)
The book attempts to present simplified means of performing the more common and most widely useful descriptive methods of regional economic analysis. It is aimed at the regional development practitioner who is operating in an environment of limited research resources.
Includes bibliographical references: p. 179-202.
rpm 16/11/2017
Loans
Keywords: Economic zoning